How can PBL promote critical thinking skills in biology material? A systematic literature review in reputable journals - Ali Usman; Kukuh Munandar; Agus Prasetyo Utomo (Research and Development in Education (RaDEn), 2024)
: The Merdeka Curriculum requires teachers to apply various learning models, including PBL, to achieve learning objectives, including critical thinking skills. However, in the context of biology learning, the application of the PBL model is rarely considered to improve students' critical thinking skills, and research on this is still limited. Therefore, this research is essential because there is no complete analysis of the impact of the PBL learning model on critical thinking skills in biology indexed by Scopus. This study uses the SLR method to investigate the effect of the PBL learning model on students' critical thinking skills in biology material. This research method follows the PRISMA model for selecting articles based on specific criteria in the SCOPUS database. The research results show that presentation and discussion methods dominate biology learning, while there is a lack of attention to students' critical thinking and a lack of electronic teaching materials. On the other hand, problem-based learning helps students understand and apply biological material and develop critical thinking skills by emphasizing the application of knowledge, analysis, synthesis, and evaluation and involving students in group discussions to motivate critical thinking. Research shows that PBL effectively improves students' critical thinking, supported by various learning models and media that strengthen students' critical thinking skills. In conclusion, applying the PBL model allows students to focus on specific topics, understand scientific concepts, and overcome challenges through data analysis, hypothesis generation, and deductive reasoning. This model encourages critical thinking and active participation of students. Teachers are expected to be able to use various learning models to improve students' thinking abilities.